The Influence of Music Tempo on Employee Productivity in Fabrication using the Cognitive Failure - Sukra, Rizka Triannisa Imasna; Tranggono, Tranggono; Sari, Rizqi Novita Sari (Borong Newinera Publisher, 2025)
This study aims to determine the effect of music tempo on work productivity and the level of cognitive failure among employees in the fabrication division of PT. Adi Joyo Kusumo. Music is used as an intervention to address boredom and stress caused by monotonous work. This research employs the Cognitive Failure Questionnaire (CFQ) method distributed to 12 employees, and observations were made on production quantities over seven days under three conditions: without music, fast tempo music, and slow tempo music. The results indicate that fast tempo music yields the highest productivity level with a total production of 26 units, followed by the no music condition (23 units) and slow tempo music (21 units). Validity tests show that all CFQ items are valid, and reliability tests yield a Cronbach’s Alpha value of 0.921, indicating reliability. ANOVA tests show a significance value of 0.000 (p < 0.05) and an F value of 17.078, indicating a significant effect of music tempo on cognitive failure levels. Although fast tempo music can enhance work performance, the noise level reached 89 dB, disturbing other divisions. This study concludes that fast tempo music can be used as a productivity enhancement strategy, provided that noise levels are controlled to avoid negative impacts on other work environments.